Two-incision Approach for the Open Reduction Internal Fixation of Intra-articular Hamate Body Fractures Using a Cannulated Headless Compression Screw. Issue 4 (December 2020) - Ha, Austin Y.; Booth, Matthew; Pet, Mitchell A.
Abstract : Fractures of the hamate are relatively rare and there is a paucity of literature describing their natural history, indications for operative fixation, surgical techniques, and outcomes. Most authors recommend operative fixation of displaced intra-articular coronal hamate body fractures, and a dorsal approach with Kirschner wires has most commonly been recommended to achieve this. In this report, a 2-incision approach to the hamate is presented that facilitates rigid internal fixation of coronal hamate body fractures with a cannulated headless compression screw and minimizes the possibility of iatrogenic injury to critical branches of the ulnar nerve. The authors summarize a series of 2 patients with displaced, intra-articular coronal hamate body fractures of differing severity treated successfully with the proposed approach.